The Impact of Differentiated Learning in the Merdeka Belajar Curriculum on Elementary School Literacy as the Object of the Kampus Mengajar Program - Bagus Adi Wijaya; Wantini; Djamaluddin Perawironegoro; Betty Mauli Rosa Bustam (Jurnal Ilmiah Sekolah Dasar, 2024)
The Merdeka Belajar curriculum emphasizes students' freedom to determine the course of learning according to their interests, needs and potential. However, it must be acknowledged that each student has a different understanding and ability in studying Islam. This research aims to analyze differentiated learning in elementary schools with the Teaching Campus program. This type of research is a quasi-experiment with a one-group pre-test and post-test design. The research subjects were 19 elementary schools. The instrument used is an essay test consisting of 15 items. Data analysis used an independent T-test assisted by IBM SPSS 25. The results of the research showed that there were differences in literacy outcomes using differentiated learning. The differentiated learning model in the Merdeka Belajar curriculum can increase literacy. Elementary schools that follow this learning model show significant improvements in literacy understanding, active participation in learning, and high learning motivation. The differentiated learning model effectively increases literacy in Elementary Schools with the Teaching Campus Program. This model can provide each student with a more relevant, exciting and practical learning experience by accommodating individual differences.